2005
DOI: 10.1097/01.tp.0000160765.66962.0b
|View full text |Cite
|
Sign up to set email alerts
|

Non???Heart-Beating Donor Kidneys in The Netherlands: Allocation and Outcome of Transplantation

Abstract: Early graft failure was significantly more likely in recipients of kidneys from NHB donors. A prolonged WIT was strongly associated with this failure. Standard allocation procedures do not have a negative effect on outcome, and there is no reason to allocate NHB kidneys differently from HB kidneys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
29
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 6 publications
8
29
0
1
Order By: Relevance
“…A generally acceptable upper limit of renal warm ischemia of 30 to 45 min was established based on experiments done in the 1970s, although more recent animal models suggest that this window may be extended up to 90 min in the nontransplant population [18,19]. Multivariate analysis of risk factors associated with early graft failure in patients receiving non-heartbeating (NHB) kidneys clearly identifies 30 min of warm ischemia as a significant risk factor [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A generally acceptable upper limit of renal warm ischemia of 30 to 45 min was established based on experiments done in the 1970s, although more recent animal models suggest that this window may be extended up to 90 min in the nontransplant population [18,19]. Multivariate analysis of risk factors associated with early graft failure in patients receiving non-heartbeating (NHB) kidneys clearly identifies 30 min of warm ischemia as a significant risk factor [18].…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate analysis of risk factors associated with early graft failure in patients receiving non-heartbeating (NHB) kidneys clearly identifies 30 min of warm ischemia as a significant risk factor [18]. Smaller case series of NHB renal transplant recipients substantiate this time limitation; however, the effect was not uniform in that some organs with greater than 30 min of warm ischemia did function well in both the short and the long term [17,18]. In addition, large animal models in which uni-nepheric animals are subjected to prolonged warm ischemia demonstrate full recovery with warm ischemia times twice that seen in NHB donors [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Concerns exist regarding the outcomes of such grafts with several groups reporting increased rates of DGF and PNF. [5][6][7] However, many series have shown encouraging short-term and medium term functional and graft survival outcomes using organs from these donors. [1][2][3][4] In addition, it has been shown that marginal kidney transplantation is associated with a significant survival benefit over that of maintenance on dialysis.…”
mentioning
confidence: 97%
“…Il s'agit d'éthique utilitariste : le bienfait collectif prime sur le bienfait individuel! Le second point fort réside dans l'étude des publications étrangères, lesquelles font état de résultats comparables à ceux des transplantations effectuées à partir de donneurs dits « classiques », à savoir en état de mort encéphalique[11][12][13][14][15]. Enfin, le protocole de l'Agence de la biomédecine a été approuvé, notamment par l'Académie nationale de médecine, le définissant comme clair et strict, respectant les dispositions légales et règlementaires, ainsi que les critères éthiques et déontologiques.…”
unclassified